Penerapan Metode Simulasi Dalam Meningkatkan Kemampuan Praktek Teknik Dasar Permainan di SMP Negeri 2 Siak Hulu - Ridhawati, Ridhawati (Komunitas Manajemen Kompetitif, 2017)
Problems faced by the teacher in giving lesson to the students of class VII especially in SMP N 2 Siak Hulu is related to the ability of students who still not optimal, this is marked by not yet achievement of KKM students in learning. In addition, the attitude of students in learning is still not enthusiasm. Through classroom action research and analyzed using qualitative techniques obtained results there is an increase in learning outcomes Penjaskes with cycle material entirely from the basic motion of basic techniques of the game, then the value of content and also practice. Based on the results of the research, 75%, 73% and 100% of 75% completeness data are found. Keywords: Simulation methods, practical skills